The color of the end : mission in the apocalypse. 2 - Iwamune, Haruo; Iwamune, Haruo (Iwamune, Haruo. The color of the end : mission in the apocalypse. vol. 2., 2025)
"As Saya continues to search for survivors, a single robot appears before her. The library it manages may be bereft of visitors, but it devotes itself to its task out of respect for the late librarian's wishes. In the face of such loyalty, the girl can't help but ponder her own seemingly endless mission. Are there still any survivors left for her to find?"--Back cover.